The answer for the exercise shown above is the first option, which is:
<span> f(x)=log(x-3)
The explanation is shown below:
If you substitute the x in the function for values, you will obtain the graph attached above. As you can see on the mentioned graph, when the variable x has the value 4, the value y is 0. Therefore, you have:
</span> f(x)=log(x-3)
f(x)=log(4-3)
f(x)=log(1)
f(x)=0<span>
</span>
Answer:
7
Step-by-step explanation:
98
<span>The number of ancestors going back through the <em>5th generation</em>, including Tle-nle and counting <em>Tle-nle as the 1st generation</em> is:
= 1 + 3 + 3^2 + 3^3 + 3^4
= (3^5 - 1) / (3 - 1)
= 242 / 2
= 121
Since we included </span>Tle-nle as the 1st generation, we will only compute up to the 4th power. If it is until the 6th generation, add 3^5 to the equation.
For this case we first define the variable:
x = number of terms.
The equation that models the problem is:
f (x) = 3.4 - 0.6x
We have then that the first four terms are:
x = 1
f (1) = 3.4 - 0.6 (1) = 3.4 - 0.6 = 2.8
x = 2
f (2) = 3.4 - 0.6 (2) = 3.4 - 1.2 = 2.2
x = 3
f (3) = 3.4 - 0.6 (3) = 3.4 - 1.8 = 1.6
x = 4
f (4) = 3.4 - 0.6 (4) = 3.4 - 2.4 = 1
Answer:
The rule for the sequence is:
f (x) = 3.4 - 0.6x
option 1